Konsep Motivasi Dalam Belajar - Anggraini, Lisa; N, Neviyarni; Nirwana, Herman (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Motivation to learn is one of the key factors that influences success in the educational process. The basic concept of learning motivation includes internal and external drives that motivate individuals to achieve educational goals and improve personal abilities. Various motivation theories, such as Maslow's needs theory, Bandura's social learning theory, and Skinner's reinforcement theory, provide an understanding of how motivation works in the context of learning. Learning motivation can be divided into two main types, namely intrinsic motivation which comes from within the individual, and extrinsic motivation which is influenced by external factors such as prizes and praise. Understanding the basic concept of learning motivation is very important for educators and students to create a more effective and productive learning environment.